Amino acid-functionalized carbon nanotube framework as a biomimetic catalyst for cleavage of glycosidic bonds. (27th February 2019) - Sugano, Yasuhito; Kuittinen, Suvi; Turunen, Ossi; Pappinen, Ari
Abstract: In this work, carbon nanotubes (CNTs) functionalized by acidic amino acids were used as a framework, which aims to form a mimetic structure of an active site of the glycoside hydrolases. It was demonstrated that the glycosidic bonds of the disaccharides were cleaved by the fabricated biofunctionalized CNTs. It was implied that the number of carboxyl groups and their individual pKa values in the amino acids, and the distance between the NH2 and the side chain carboxyl groups of the amino acid are predominant factors for determining the reaction efficiency and the optimum pH. It was suggested that glutamic acid functionalized CNTs framework showed the highest efficiency in the cleavage of glycosidic bond of cellobiose than other acidic biomolecules. It was also suggested that the glutamic acid functionalized CNT framework showed preference to the types of glycosidic bonds in the following order: β -1, 2-glycoside > β -1, 4-glycoside > α -1, 4-glycoside α -1, 1-glycoside bond.